A descriptive study on the emotion work among call center agents in Iloilo City. - Abelarde, Ma. Gail C.
This study focused on the nature of call center agents in Iloilo City. It described the different techniques and procedures employed by agents when interacting with clients such as surface and deep acting, cognitive, and bodily techniques. Ervin Goffman?s theory on Impression Management and Arlie Hochschild?s theory on Emotion Work were used as frameworks to understand the nature of emotion work employed by call center agents. The researchers purposively selected twenty-five (25) call center agents in Iloilo City. Twelve (12) of which were handling inbound calls, and thirteen (13) of them were handling outbound calls. A thematic analysis was utilized to interpret and analyze the data gathered from the focus group discussion (FGD) conducted. The results showed minimal differences in the techniques and procedures provided by the companies in inbound and outbound call centers. Inbound agents spend less time going into emotion work because their primary focus was more on being knowledgeable about the product that their company markets for them to be able to answer to queries from their clients. On the other hand, outbound agents spend more time going into emotion work because not only they needed to be knowledgeable about the product that their company markets, but they also have to be able to persuade their clients into purchasing the product. In line with this, those who worked as outbound agents experienced much burden due to high performance standards due to the quota they need to attain in their required sales.